INTRODUCTION THE NEW WELDING TECHNOLOGIES AND MATERIALS FOR WELDING ROLLED METAL BY HIGHER DURABILITY - Synieok, O. H.; Herasymenko, A. M.; Riabokon, V. D.; Riabtsev, K. V.; Korzin, K. Yu.; Zdorenko, O. V. (Science and Transport Progress, 2010)
Welding materials, which are as a rule used for making the responsible metal constructions, do not always meet the high indices of rolled steel properties of durability classes С355-490 MPa. In the paper the research results of application of welding materials produced by the firm «ESAB» for the automatic flux welding of rolled steel 06Г2Б ТУ В 27.1-05416923-085:2006 are presented.